Body and repetitive memory in autism - de Sousa, Cleuber Cristiano; Novaes, Joana de Vilhena (Seven Editora, 2023)
Objective: The objective of this work is to present the body as a memory of repetition in Autism and what would be the consequences arising from placing this body in relation to the internal and external world, with spaces, others and oneself. Methodology: The meaning can always be different and, in the specificity of the constitution of the autistic subject. Thus, the production of meanings is understood in comparisons, relations, dissonances, approximations and displacements. It is in the event and in the analysis of other materialities (non-linguistic) that we will present the results. Results: The experiential experiences of childhood and the relationships between mother and baby are paramount for the subjective constitution and the production of meanings in the formation of the psyche. The affective life, the emotions, the identifications and the strengthening of the bonds of social belonging are anchored in this phase and from there emanate all the threads that link the unconscious content. The study of the history of the mother A.S. and her relationship with the little R.A. demonstrated that the child with autism is constituted in the regressive and partial primary and secondary identifications, with a singularity of its own constituted in the repetition. The symbolic and imaginary contents to remember and repeat are repeated without success in the elaboration. Conclusion: From the personal history of the mother A.S. and the son R.A., all the premises about the affective life, formation of the psyche and unconscious come from the studies of Sigmund Freud and the successor psychoanalysts who affirmed or refuted his writings, contributing to psychoanalysis becoming a theory in process. The case study presented in this paper is about the four-year-old R.A. and his mother, his personal history and the constitution of a subjective body in the memory of repetition. DOI:https://doi.org/10.56238/innovhealthknow-016